Pengaruh Instagramable Place dan Product terhadap Minat Beli - Isa, Isa (Universitas Darwan Ali, 2024)
The purpose of this research is to analyze the effect of Instagrammable Place and Instagrammable Product on buying interest. The population of this research is visitors who come to Bapinang Coffee Shop and Eatery. The research sample is 100 respondents taken by purposive sampling technique. The research instrument was a questionnaire and was analyzed using multiple regression. Based on the results of the analysis, it was found that Instagramable Place had no significant effect on purchase intention, while the Instagramable product variable had a positive effect on consumer purchase intention at Bapinang Kopi and Eatery.